100 Hz Electroacupuncture Alleviated Chronic Itch and GRPR Expression Through Activation of Kappa Opioid Receptors in Spinal Dorsal Horn - Li, Hong-Ping; Wang, Xiao-Yu; Chen, Chao; Li, Jing-Jing; Yu, Chi; Lin, Li-Xue; Yu, Zi-E; Jin, Zhi-Yuan; Zhu, He; Xiang, Hong-Chun; Hu, Xue-Fei; Cao, Jie; et al. (Frontiers in Neuroscience, 2021)
Background Clinical studies have shown that electroacupuncture (EA) alleviates chronic itch. Gastrin-releasing peptide receptor (GRPR) and dynorphin (DYN) in the spinal dorsal horn positively or negatively regulate itch, respectively. However, which frequency of EA is effective on relieving chronic itch and reducing the expression of GRPR, whether DYN-A in the spinal cord is involved in the underlying mechanism of the antipruritus effect of EA remains unknown. Methods The mixture of acetone and diethyl ether (1:1) [designated as AEW (acetone/diethyl ether and water) treatment] was used to induce the dry skin model of chronic itch. EA was applied to Quchi (LI11) and Hegu (LI4). Western blot was used to detect the expression of GRPR and DYN-A. Immunofluorescence was used to detect the expression of DYN-A. Results The AEW administration induced remarkable spontaneous scratching, enhanced the expression of GRPR, and reduced the expression of DYN-A. Compared with the sham EA, 2 Hz EA, or 15 Hz EA group, 100 Hz EA was the most effective frequency for relieving chronic itch, reducing the expression of GRPR, and increasing the expression of DYN-A in the cervical dorsal horn. Furthermore, intraperitoneal injection of kappa opioid receptors (KORs) antagonist nor-Binaltorphimine dihydrochloride (nor-BNI) significantly reversed the effect of 100 Hz EA on the inhibition of both itching behavior and GRPR expression. Conclusion EA at 100 Hz is the most effective frequency that inhibits chronic itch and GRPR expression through activation of KORs in the spinal dorsal horn, which can effectively guide the clinical treatment and improve the antipruritic effect of acupuncture.